FAKTOR-FAKTOR PENERAPAN KESELAMATAN DAN KESEHATAN KERJA YANG MEMPENGARUHI KINERJA PROYEK KONSTRUKSI GEDUNG DI PROVINSI ACEH - Bunial Bunial; Muttaqin Muttaqin; Anita Rauzana (Prodi Magister Teknik Sipil Unsyiah, 2018)
PT. Jamsostek stated that in 2012 everyday there are 9 workers who died due to accidents, while total work accident in the same year recorded 103,000 cases. Accidents to these workers will certainly make the productivity of project work decreased, as well as will impact on the poor performance of the project. This study aims to identify the dominant OSH factors applied in the implementation of building construction projects in Aceh Province, and to analyze the relationship and influence between the factors of OSH implementation on the performance of building construction projects in Aceh Province. This study uses qualitative methods through interviews and quantitative through the distribution of questionnaires. The number of research samples obtained by 68 contractor companies. The sampling technique used is purposive sampling. Data processing methods consist of test validity, and reliability, while data analysis consists of descriptive analysis, simple correlation and multiple linear regression. The results showed that the dominant K3 factor applied in the implementation of the building construction project in Aceh Province was a public protection factor with a mean of 4.632. The safety and work competence factors have a good relationship with Spearman coefficient of 0.451 and 0.429, the factors of equipment and work clothes, vehicle lanes, and equipment and machinery have a low correlation with Spearman coefficient of 0.328, 0.386, and 0.243, while fire, and sound, public protection, general, occupational health, and seriousness of the company have a very low relation with Spearman coefficient of 0.077, 0.130, 0.066, 0.107, 0.121, and 0.169 to the performance of building construction projects in Aceh Province. The influence of OSH implementation factors on the performance of building construction project in Aceh Province, which has significant effect is safety factor, equipment and work clothes, vehicle path, equipment and machinery, public protection, general, seriousness of company, and worker competence with tcount greater than ttable and significance value lower than 0.05.